Lactobacillus paracasei S16 Alleviates Lumbar Disc Herniation by Modulating Inflammation Response and Gut Microbiota - Wang, Zhanchao; Wu, Huiqiao; Chen, Yu; Chen, Huajiang; Wang, Xinwei; Yuan, Wen (Frontiers in Nutrition, 2021)
Lumbar disc herniation (LDH) is a common cause for low back pain. In this study, we aimed to explore the effects of a specific Lactobacillus paracasei (L. paracasei), L. paracasei S16, on the symptoms of LDH using a mouse model of LDH. The results showed that L. paracasei S16 treatment improved the behavior, increased the cell proliferation, and decreased the apoptosis in LDH mice. Moreover, L. paracasei S16 treatment alleviated the aberrant inflammation response in the LDH mice, which is characterized by the decreased anti-inflammatory cytokines, increased pro-inflammatory cytokines, and decreased percentage of Th1 and Th2 cells and Th17/Treg ratio. 16S rRNA sequencing results showed that the LDH mice treated with L. paracasei S16 have higher relative abundance of Lachnospiraceae and Ruminococcaceae and lower abundance of Lactobacillaceae than mice in the LDH group. Additionally, the serum metabolites involved in the linoleic acid metabolism, alanine. aspartate, and glutamate, glycerophospholipid, and TCA cycle were significantly decreased and the metabolite involved in purine metabolism was significantly increased after the L. paracasei S16 treatment in the LDH mice. These results showed that administration of L. paracasei S16 can improve inflammation response, alter gut microbiota, and modulate serum metabolomics in a mouse model of LDH.